Prognostic value of high thymidine kinase activity in patients with previously untreated diffuse large B-cell lymphoma treated by rituximab, cyclophosphamide, doxorubicin, vincristine and prednisolone. Issue 11 (November 2013) - Suzuki, Kazuhito; Terui, Yasuhito; Yokoyama, Masahiro; Ueda, Kyoko; Nishimura, Noriko; Mishima, Yuko; Sakajiri, Sakura; Tsuyama, Naoko; Takeuchi, Kengo; Hatake, Kiyohiko
Abstract The purpose of this study was to investigate prognostic factors for overall survival (OS) among patients with previously untreated diffuse large B-cell lymphoma (DLBCL) treated with rituximab, cyclophosphamide, doxorubicin, vincristine and prednisolone (R-CHOP). We evaluated four biological parameters, including thymidine kinase (TK) activity. This study included 183 patients. The median level of TK was 14.0 IU/L, which we chose as the cut-off. After a median follow-up time of 50.0 months, the OS rate at 4 years in the high and low TK arm were 46.7% and 66.7%, respectively (p = 0.001). By multivariate analysis, OS was significantly inferior in the high TK arm (hazard ratio 2.705; p = 0.045). The complete response (CR) rate in the high TK arm was significantly worse than in the low TK arm. OS was significantly better in patients who had achieved CR than in those with partial response or less. In conclusion, high TK activity was a strong predictor for short OS and poor response among patients with previously untreated DLBCL treated with R-CHOP.